Effects of copper sulphate administration on body weight gain and some blood parameters in lambs - Sahín, T; Çimtay, I; Aksoy, G; Ölçücü, A (Scientific Technical Research Council Turkey, 2001)
The objectives of this study were to determine the effects of copper sulphate administration on body weight gain and some biochemical, haematological parameters in lambs which had serum copper levels at subclinical values. This study was performed on 30 Ivesi male lambs (control group: 12, experimental group: 18). aged with 15-20 days. In the experimental group. 100 mg copper sulphate (1% solution) was administered orally four times (with periods of two weeks). Blood samples were collected on 0, 14, 28, 42, 56th days and body weight of lambs was determined. Copper administration caused significant increases in weight gain, haemoglobin and serum copper levels. However, it did not affect haematocrit, serum zinc, iron, calcium and magnesium values in lambs.
Kuzularda Canli A?irlik Kazanci ve Bazi Kan Parametreleri Üzerine Bakir Sülfat Uygulamasinin Etkileri
Keywords: copper sulphate; biochemical and haematological parameters; body weight; lambs